Jacob have I loved - Paterson, Katherine (New York : Crowell, 1980)
Feeling deprived all her life of schooling, friends, mother, and even her name by her twin sister, Louise finally begins to find her identity.
Newbery medal, 1981
Keywords: Twins -- Fiction; Sisters -- Fiction; Identity (Philosophical concept) -- Fiction; Newbery Medal; Chesapeake Bay Region (Md. and Va.) -- Fiction